Islamic Law as a Foundation of Halal Industry: The Role of Shariah-Driven Governance in Enhancing Industry Competitiveness - Mahsun, Moch (Moderasi : Journal of Islamic Studies, 2025)
The halal sector is emerging on a global scale, expanding into other industries including pharmaceuticals, cosmetics, logistics, finance, and travel. This study examines the Islamic law from the shariah governance perspective and its foundation on the halal industry’s competitive advantage. Having utilized a literature based methodology, the study integrates and synthesizes islamic jurisprudence, policy and regulations, technology and consumers, and empirical studies undertaken from 2015 to 2025. The study concludes that halal certification is a competitive advantage only when Islamic law is embedded with foundational regulations, effective controls, and a fetwa system. The study also suggest that the artificial intelligence, block chain and digital certification improve governance transparency and traceability. The study concludes that Islamic law is a religious requirement but also serves as a strategic governance framework that enhances global competitiveness.